A biomimetic synthesis of homofascaplysin C from ditryptophans. Issue 11 (16th March 2016) - Xu, Mei; An, Rui; Huang, Tao; Hao, Xiao-jiang; Liu, Sheng
Graphical abstract: Abstract: A route for the biomimetic synthesis of homofascaplysin C has been established. The key strategy is based on the chemoselective and sequential oxidative cleavage of two side-chains of the ditryptophan precursor.